OPTIMIZATION OF EXTRACTION CONDITIONS FOR PHENOLIC COMPOUNDS FROM LEAVES OF CAMELLIA DALATENSIS LUONG, TRAN & HAKODA - Huỳnh Đình Dũng; Lữ Hoàng Trúc Linh; Lương Văn Dũng; Nguyễn Thị Tố Uyên; Trịnh Thị Điệp (Tạp chí Khoa học Đại học Đà Lạt)
The extraction conditions of polyphenols from Camellia dalatensis leaves were optimized by experimental design with five variables using Design-Expert V11.1.0.1 software. Using the methodology of response surface optimization, the optimal polyphenol extraction conditions were found to be an ethanol concentration of 49.29%, temperature at 60°C, a sonication time of 40min, a material size of 0.5mm, and a solvent/material ratio of 5.47.